MEASURES TO PROTECT THE ENVIRONMENT FROM THE HARMFUL EFFECTS OF MOTOR TRANSPORT (European Journal of Emerging Technology and Discoveries, 2023)
In this article, the problems associated with the high oxidizing activity of the air characteristic of the Aral Bay region are studied. Such conditions lead to accelerated corrosion of car parts, increased maintenance and current maintenance labor and need for spare parts, reduced vehicle life and maintenance intervals, and the consequences have been studied.